Formation of heat tolerance in cotton cultivars through enhancement of antioxidant defence by a natural glycyrrhizin–salicylic acid complex - Karomat, K; Ali, A; Sanjar, N; Nigora, K; Dildora, B (Plant Science Today, 2026)
Heat stress cause large and recurrent economic losses in cotton production. We hypothesised that a natural glycyrrhizic–salicylic acid complex applied at nanomolar concentration would mitigate heat-induced oxidative damage, activate enzymatic antioxidants and improve biomass recovery across diverse cotton cultivars. Seedlings experienced acute heat stress (45 °C for 6 hr) followed by 24 hr recovery at 30 °C. We quantified growth (root/shoot biomass), hydrogen peroxide and malondialdehyde as damage markers and activities of superoxide dismutase, catalase and peroxidase. Treatment consistently decreased oxidative markers by ~40–60 % and increased antioxidant activities; biomass recovery improved across cultivars. At the field scale, using Uzbekistan-relevant economics, a conservative yield gain of 5–7 centners ha-1 of seed cotton (0.5–0.7 t ha-1) with a 33 % lint turnout converts to 0.165–0.231 t ha-1 additional fibre. Using recent international cotton prices (~0.66 USD lb-1 ≈ 1.46 USD kg-1), this equals 240–337 USD ha-1 extra revenue; after deducting treatment cost (125 mg ha-1 ≈ 24 USD ha-1), the net margin gain is ~215–313 USD ha-1. These findings indicate an environmentally safer and economically promising strategy to stabilise yields during heat extremes.